2021
DOI: 10.1159/000515817
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab and Bevacizumab in Patients with Unresectable Hepatocellular Carcinoma: Pharmacokinetic and Safety Assessments Based on Hepatic Impairment Status and Geographic Region

Abstract: <b><i>Introduction:</i></b> Phase 1b GO30140 and phase 3 IMbrave150 studies evaluated first-line atezolizumab + bevacizumab for unresectable hepatocellular carcinoma (HCC). Here, we evaluated pharmacokinetics (PK) and safety by hepatic impairment status and geographic region. <b><i>Methods:</i></b> Patients received atezolizumab 1,200 mg + bevacizumab 15 mg/kg IV every 3 weeks. Drug concentrations were evaluated by descriptive statistics and population PK. PK and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The indirect comparison of safety data between CheckMate 040 cohort 5 (Child-Pugh B7/8 patients, except 1 Child-Pugh A6 patient in the sorafenib-naïve arm; nivolumab monotherapy) and CheckMate 040 cohorts 1 and 2 (98% Child-Pugh A) did not show a significant difference in trAE incidence between Child-Pugh A or B patients (Child-Pugh B cohort vs. Child-Pugh A cohort all-grade trAE incidence: 51 vs. 59%) [ 22 ]. Similar results were reported in a post hoc analysis for GO30140 and IMbrave150 trial (atezolizumab plus bevacizumab), where the investigators found patients with moderate hepatic impairment have similar trAE incidence compared to overall population (moderate hepatic impairment vs. overall population: 96.4 vs. 98.2%) [ 53 ]. There are currently no published articles on the impact of baseline liver function on trAE in patients under dual ICI therapy or ICIs plus oral targeted agents, but analyses focusing on oral targeted agent monotherapies indicate that impaired liver function would raise important safety issues in this subpopulation [ 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 81%
“…The indirect comparison of safety data between CheckMate 040 cohort 5 (Child-Pugh B7/8 patients, except 1 Child-Pugh A6 patient in the sorafenib-naïve arm; nivolumab monotherapy) and CheckMate 040 cohorts 1 and 2 (98% Child-Pugh A) did not show a significant difference in trAE incidence between Child-Pugh A or B patients (Child-Pugh B cohort vs. Child-Pugh A cohort all-grade trAE incidence: 51 vs. 59%) [ 22 ]. Similar results were reported in a post hoc analysis for GO30140 and IMbrave150 trial (atezolizumab plus bevacizumab), where the investigators found patients with moderate hepatic impairment have similar trAE incidence compared to overall population (moderate hepatic impairment vs. overall population: 96.4 vs. 98.2%) [ 53 ]. There are currently no published articles on the impact of baseline liver function on trAE in patients under dual ICI therapy or ICIs plus oral targeted agents, but analyses focusing on oral targeted agent monotherapies indicate that impaired liver function would raise important safety issues in this subpopulation [ 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 81%
“…CRCL was calculated from the baseline serum creatinine using the Cockcroft–Gault formula 10 capping CRCL at 150 ml/min. The NCI liver function classification was based on bilirubin and ALT levels 11 …”
Section: Methodsmentioning
confidence: 99%
“…The NCI liver function classification was based on bilirubin and ALT levels. 11 In addition, food intake and formulation were considered as covariates and their values were given by the designs of the studies. Altogether, each subject was associated with 13 covariates.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…According to the IMbrave150 trial, atezolizumab in combination with bevacizumab showed greater benefits compared with sorafenib in advanced HCC patients and suggested that this combination strategy could be used as the first-line standard of care. [310][311][312][313] Additionally, a combination of ICB with other targeted therapeutic approaches, including ATR kinase inhibition and androgen receptor blockade resulted in synergistic therapeutic response in prostate cancer. [314][315][316] Combining chemotherapy with ICB can be used to extend a synergistic therapeutic effect.…”
Section: With Immune Checkpoint Blockade (Icb)mentioning
confidence: 99%